INTELLIGENT ANALYZER FOR UNATTENDED OBJECT DETECTION - Khadse, Rutuja Y.; Lokhande, S.S.; Koti, S.A. (International Journal of Research -GRANTHAALAYAH, 2015)
In recent year’s surveillance system have become more popular in the field of computer vision. An object which is left at a particular place under surveillance and unattended over a period of time is called unattended object. Places like airports, railway stations, big shopping malls etc. where there is potentially high security threat detecting unattended object is a very important. The main aim of project is to develop intelligent vision based analyserbased on MATLAB using Image processing for unattended object detection.The detection is based on a simple mathematical model and works efficiently. The pre-processing involves a dual-time background subtraction algorithm which dynamically updates two sets of background, one after a very short interval and the other after a relatively longer duration. The framework of the proposed algorithm is based on the Approximate Median model.